Pengembangan Kompetensi Guru melalui Kegiatan Lesson Study Berbasis Sekolah di SDN 02 Karangmulya Malangbong Garut - Dede Maskur; Ejen Jenal Mutaqin (Institut Pendidikan Indonesia, 2023)
The decentralization of education provides opportunities for schools in the regions. School policy making is inherent in the autonomy of the principal. The school principal has the authority to translate policies from higher leadership in accordance with the school's vision, mission and goals which refer to resources inside and outside the school. In response to the above policy, with the authority that belongs to the school principal, one of the policies developed and implemented at SDN Karangmulya 02 Malangbong District, Garut Regency is